2009
DOI: 10.1007/s10661-009-0789-9
|View full text |Cite
|
Sign up to set email alerts
|

Carbon monoxide and carbon dioxide concentrations in Santiago de Chile associated with traffic emissions

Abstract: CO/CO(2) ratios have been measured in different locations of Santiago de Chile city. Measurements were carried out in a tunnel (prevailing emissions from cars with catalytic converter) and close to heavy traffic streets. Concentrations measured along the city traffic tunnel or temporal profiles of concentrations measured near heavy traffic streets allow an estimation of CO/CO(2) ratios emitted from mobile sources. Values obtained range from 0.0045 +/- 0.0006 to 0.0100 +/- 0.0004 and depend on the prevailing ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 11 publications
1
6
0
Order By: Relevance
“…A similar magnitude was found for rush hour times in previous studies in Los Angeles (Newman et al, 2013). Rubio et al (2010) and reference therein report CO/CO 2 emission ratios of 0.009 AE 0.005 kg CO/kg CO 2 as typical for catalytic cars and of 0.003 AE 0.001 kg CO/kg CO 2 as typical for Figure 14. Diurnal variation of CO/CO 2 ratio for light-duty gasoline and heavy-duty diesel vehicles calculated using MOVES.…”
Section: Resultssupporting
confidence: 87%
“…A similar magnitude was found for rush hour times in previous studies in Los Angeles (Newman et al, 2013). Rubio et al (2010) and reference therein report CO/CO 2 emission ratios of 0.009 AE 0.005 kg CO/kg CO 2 as typical for catalytic cars and of 0.003 AE 0.001 kg CO/kg CO 2 as typical for Figure 14. Diurnal variation of CO/CO 2 ratio for light-duty gasoline and heavy-duty diesel vehicles calculated using MOVES.…”
Section: Resultssupporting
confidence: 87%
“…Many of these compounds are highly carcinogenic at relatively low levels, and UFP associated with vehicular emissions have been observed to cause oxidative stress in cells and may be linked to adverse health effects. Several studies have reported measurements of PAH emission factors (EFs) associated with the particle phase from engine exhaust emissions. However, a few have examined size-resolved PAH concentrations in the nuclei-mode. For decades, engine exhaust EFs have been measured from vehicles submitted to dynamometer tests or from samples collected in urban tunnels that represent local traffic patterns. Dynamometer testing provides valuable information on a variety of parameters including the effects of engine technologies, fuel and additives composition, vehicle acceleration, engine displacement, operating temperature, and dilution ratio from individual vehicles. On-road tunnel measurements provide EFs that reflect the contribution from a vehicular fleet that represents local traffic.…”
Section: Introductionmentioning
confidence: 99%
“…On-road tunnel measurements provide EFs that reflect the contribution from a vehicular fleet that represents local traffic. Measurements from “car-chasing’’ experiments can be performed directly behind moving vehicles to obtain EFs of individual vehicles under real-world driving patterns and conditions. The information obtained using different approaches are useful when a particular situation is sought. A limited number of EFs have been reported for vapor-phase and particle number concentration for European, American, and Chinese vehicles. ,,, Comprehensive studies of the particle size distribution and the effects of vehicle fuels on PAH EFs were reported by Marr et al and Miguel et al, for samples collected in the same tunnel as the present study, using a low pressure impactor with a lower diameter size cut of 0.050 μm.…”
Section: Introductionmentioning
confidence: 99%
“…As a preface, we discuss the CO emission factor implied by the Table 1 value of 0.0033 kg(CO)/kg(CO 2 ), or equivalently the concentration ratio of 5.2 ppbv/ppmv reported by Rappenglück et al (2013), each of which converts to an emission factor of 10 g(CO)/kg(fuel). Rappenglück et al cite Newman et al (2013) and Rubio et al (2010) (Wunch et al, 2010). This ratio includes contributions from other combustion sources in addition to vehicles (although care was taken to remove influence of wildfires) and if it were converted to an emission factor it would yield 22 g(CO)/kg(fuel).…”
Section: Time Series and Correlation Plots For Examples Of Accepted Amentioning
confidence: 99%